Three new species of Eupithecia Curtis from Arizona and New Mexico with discussion of associated species (Lepidoptera: Geometridae: Eupitheciini) - Ferris, Clifford D. (Zootaxa, 2007)
Eupithecia macfarlandi, new species, and Eupithecia penablanca, new species, from southern Arizona, and Eupithecia nonanticaria, new species, from southwestern New Mexico, southeastern Arizona, and Chihuahua, Mexico are described. Adults and male and female genitalia are illustrated. Eupithecia anticaria Walker and E. nonanticaria are compared.